Kepemimpinan dalam Menunjang Peningkatan Kinerja: Studi Kasus UMKM - Cahyani, Rusnandari Retno (Universitas Sahid Surakarta, 2017)
Leadership is critical to successful implementation in supporting the success of MSMEs. MSMEs will be authentic to entrepreneurship where individuals or groups will make products or services to create more value and are needed by the market. So that leadership determines the success of the performance of MSMEs themselves. Various industrial fields were studied both from micro, small, and medium scale businesses. The results show that each field of industry has a characteristic need for leadership, which is also influenced by culture and the level of spirituality in the leadership. In the Food and beverage industry, the characteristics of family leadership while in the fashion or clothing industry, the characteristics of leadership are rigor and honesty.